(untitled) (EconoPulse Nexus : Journal of Economics, Business, and Finance, 2025)
This study aims to examine the effect of financial literacy and access to capital on the financial performance of MSMEs in Madura. Using a quantitative research method through a survey, 250 MSMEs were selected using purposive sampling from all districts in Madura. Data were collected through a structured questionnaire and analyzed using SPSS software through descriptive and regression analysis. The results show that financial literacy has a positive and significant effect on the financial performance of MSMEs. This confirms that the ability of business actors to understand, plan, and control financial aspects is a key factor that can improve the effectiveness of resource management and strengthen business performance. Conversely, access to capital does not have a significant effect on financial performance and even tends to show a negative direction. This condition indicates that the availability of capital without proper management can actually create a new burden for MSMEs, especially in relation to loan obligations and the mismatch between financing and business needs. This finding underlines the importance of financial literacy as the main foundation in utilizing capital productively, so that improving the financial performance of MSMEs does not solely depend on access to capital, but on the ability to manage it effectively and sustainably.